Analisis Faktor – Faktor Terjadinya Pembiayaan Bermasalah Tanpa Agunan dan Strategi Penanganannya Di Lembaga Keuangan Mikro Syariah Dokma Kampus Center Pasuruan - lutfiyah; Hilda Sanjayawati; Saiful Bakhri (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2023)
The purpose of this study was to find out what are the factors that cause problematic financing on qardhul hasan products and how to deal with problematic financing on qardhul hasan at the Dokma Islamic microfinance institution, Pasuruan Center Campus. In an effort to achieve these goals, this study uses a qualitative descriptive approach in collecting data. The authors use primary data sources taken from observation and interviews, as well as secondary data in the form of literature studies and other documentation.The results of this study are that what causes problematic financing in qardhul hasan financing products at the Dokma Syariah Center Campus Pasuruan Microfinance Institution are internal factors and external factors. Internal factors are the inaccuracy of financing officers or cooperatives in analyzing the character of prospective members, and external factors are factors that occur outside of the bank's fault, external factors are also due to the intentional element of financing members not paying installments and unintentionally, namely natural disasters such as death is one of the causes of financing without collateral problems. In handling problematic financing on qardhul hasan products, it is necessary to use a rescheduling system, a reconditioning system or changes to requirements for returns and restructuring. By using these three systems, the Dokma Campus Center Pasuruan Islamic microfinance institution can reduce losses that occur or are experienced by the Dokma Campus Center Pasuruan Islamic microfinance institution in providing financing without collateral.